2019
DOI: 10.1021/acssuschemeng.9b03731
|View full text |Cite
|
Sign up to set email alerts
|

Fe–Ni Layered Double Hydroxide Arrays with Homogeneous Heterostructure as Efficient Electrocatalysts for Overall Water Splitting

Abstract: Design and synthesis of highly efficient, stable, and low-cost catalysts have a crucial role in the study of electrolytic water. In this work, a novel Fe–Ni layered double hydroxide (LDH) material with homogeneous heterostructures is successfully synthesized by a two-step hydrothermal method. Compared with the ordinary Fe–Ni LDH arrays prepared by one step, this structure has a rougher surface, so it has a more extensive active area, thus providing more active sites. Due to the synergistic effect of different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Earth‐abundant transition metal layered double hydroxides (LDHs) have been recognized as promising electrocatalysts for overall water splitting in alkaline media. [ 5–8 ] Stahl and co‐workers [ 9 ] found that in NiFe LDH electrocatalysts, water oxidation occurred at reactive Fe 4+ species generated at edge, corner, or defect sites within Fe‐doped NiOOH lattice. However, their relatively inferior conductivity, sparse catalytic edge sites, and surface electronic structure and density limit the electrocatalytic performance.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Earth‐abundant transition metal layered double hydroxides (LDHs) have been recognized as promising electrocatalysts for overall water splitting in alkaline media. [ 5–8 ] Stahl and co‐workers [ 9 ] found that in NiFe LDH electrocatalysts, water oxidation occurred at reactive Fe 4+ species generated at edge, corner, or defect sites within Fe‐doped NiOOH lattice. However, their relatively inferior conductivity, sparse catalytic edge sites, and surface electronic structure and density limit the electrocatalytic performance.…”
Section: Figurementioning
confidence: 99%
“…As a result, the catalyst achieved a voltage of 1.88 V at the current density of 50 mV cm −2 toward overall water splitting. [ 6 ]…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…However, in this work, OER has become an asset next to the battery functionality which makes other cation choices interesting. Iron offers the advantage of a good stability at the trivalent state 30 ; as well as a high OER catalytic behaviour when combined with Ni as Fe-NiOOH [31][32][33][34][35] . Indeed, recently NiFe-LDH has gained increasing attention in the water oxidation field and is now recognized as one of the most promising OER catalysts for alkaline media 36,37 .…”
Section: Introductionmentioning
confidence: 99%
“…Tremendous research efforts have been devoted to the design and development of transition metal‐based substances for water decomposition catalysis, e. g. sulfides, [17,18] carbides, [19] phosphates, [3,20,21] borides, [22] hydroxides, [23–25] metal oxides [26] and so on [27,28] . Well‐known layered double hydroxides (LDHs) such as NiFe‐LDH, [29–31] NiCo‐LDH, [32,33] NiMn‐LDH, [34] NiTi‐LDH, [35] NiV‐LDH [36,37] have also been deemed as “star materials” for many years with impressive catalytical performances due to their large surface area and the adjustable chemical composition in layered structure. Puzzlingly, NiAl LDH as a host material towards water decomposition did not inherit the excellent catalytical ability but with sluggish water‐decomposition kinetics and relatively poor electrocatalytic activity [38] .…”
Section: Introductionmentioning
confidence: 99%